Does destination promotion on social media affect visit intention? Empirical study on Instagram - Andri Dayarana K. Silalahi; Edgar Octoyuda; Pantas H. Silaban; Lamtiur Hutabarat (Jurnal Manajemen dan Pemasaran Jasa, 2022)
In today's economy, social media can be a valuable tool for businesses to conduct various marketing activities. In particular, social media marketing is imperative for tourism as it helps with branding, increasing awareness, and driving visitors. In this way, social media can be used in marketing communication, media promotion, and reaching more target consumers. A limited number of studies have investigated the topic of destination promotion from the tourism marketing perspective. As a result, social media has become a popular media reference that influences consumers' decision-making processes. This study aims to investigate how the promotion of beach destinations on social media affects destination attractiveness, destination image, and visit intention. This study examined the hypotheses of 320 respondents who possess Instagram accounts and have visited beach tourist destinations due to Instagram promotions. Smart-PLS 3.0 was used to examine the hypothesis using the structural equation modeling method. Test results indicate that promoting destinations on social media can significantly influence their attractiveness and public perception. When consumers believe that a destination is attractive, it will positively impact the destination's image. Furthermore, the destination image can significantly impact the visit intention. As a result, the findings of this study suggest that tourism businesses use the findings as an effective means to develop a positive image of a destination that is attractive. Furthermore, this study contributed to how tourism marketing businesses and researchers may be able to use Instagram to generate interest in visiting.